Patrons, parties, political linkage and the birth of competitive-authoritarianism in Africa - Cheeseman, N (Cambridge University Press, 2015)
Few scholars have taught us more about African voters, legislators, and legislatures than Joel Barkan. Drawing on Barkan’s analysis, the first part of this article argues that the African one-party state can be usefully viewed as a competitiveauthoritarian system underpinned by a form of political linkage that allows for elements of coercion and competition. Building on this framework, the second part demonstrates that the political linkage structures that emerged in singleparty systems such as those of Kenya, Senegal, and Tanzania have played an important role in shaping the dynamics of multiparty politics and the prospects for democratic reform